1964
DOI: 10.1126/science.144.3623.1240
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Leaf Movements: Persistence in Bean Plants Grown in Continuous High-Intensity Light

Abstract: A circadian leaf movement has been found in Phaseolus vulgaris var. Pinto that will persist under constant temperature and continuous fluorescent light. The period of leaf movement was approximately 26 hours in length, and the amplitude did not diminish for at least 4 weeks. Leaf movements were similar for plants grown in either 1100, 4950, 7700, or 10,450 lumens per square meter. This is the first clearly defined persistent circadian rhythm reported for leaves of higher plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

1965
1965
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 3 publications
1
16
0
Order By: Relevance
“…Although the circadian leaf movements for the two leaves on the same plant were usually closely in phase, they could be several hours out of phase, as observed previously by Hoshizaki and Hamner (8). Likewise, the movement of one plant was not necessarily synchronized with the movement of another plant (Fig.…”
Section: Materiails and Methodssupporting
confidence: 51%
See 1 more Smart Citation
“…Although the circadian leaf movements for the two leaves on the same plant were usually closely in phase, they could be several hours out of phase, as observed previously by Hoshizaki and Hamner (8). Likewise, the movement of one plant was not necessarily synchronized with the movement of another plant (Fig.…”
Section: Materiails and Methodssupporting
confidence: 51%
“…The movement rhythms are present under constant light and temperature conditions (2,4,7). Under continuous light these rhythmic movements have been recorded for a period of 4 weeks (8). It is assumed that these circadian movements are endogenous to the plant and that the "internal oscillator" (2) is expressed without any environmental stimuli.…”
mentioning
confidence: 99%
“…Rhythmic activity was generally observed for at least 6 days and for as long as 9 days in some plants. This is in contrast to circadian rhythm activity which began immediately when the leaves unfolded and was observed for as long as 28 days (9).…”
Section: Resultsmentioning
confidence: 71%
“…Even though this study was initiated to learn more about circadian leaf movements such as those reported by Hamner (7), Hoshizaki (8), and Trouse (12), the shorter interval movements became more interesting. Because the short interval rhythms have been noted in Desmodium gyrans, beans (1, 2), cotton (6), and about 40 other types of plants (4), they are undoubtedly important physiologically.…”
Section: Discussionmentioning
confidence: 99%